Innovative Agricultural Technologies for Sustainable Food and Environment: A Mini Review - et. al., Mohd Danish Ahmad , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Agriculture and food systems have high risk of food and nutrition security due to rapid increasing human population and to protect environment from being exploited. Hence, new technologies must be adopted in agricultural system that meet increasing demand of food, reduction in malnutrition and are ecologically sustainable. Enriched plant growth promoting rhizobacteria (PGPR) have proven capabilities for sustainable agricultural techniques and they also reduces the potential threats to soil, water and air environments. PGPR acts as a catalyst to enhance the growth of the plants. The impacts of natural and edaphic parameters like temperature extremities, climate change condition and salinity and the serious threat posed by fertilizers to environment as they release harmful chemicals into air, water, and soil. This led to the advent of environmentally sustainable alternative or biofertilizers. Water management models in agriculture targets to reduce water wastage by determination of accurate water requirement by the crop and to increase the performance of water distribution by adoption of precise irrigation techniques, thus becoming an efficient solution for drylands. Information technology brought a revolution in the agricultural world. Development of mathematical models for crops which hold the dynamic relation between plant, weather conditions, soil, and management operations leading sustainable agriculture, would assist to tackling emerging issues of food security, strategy evaluation and farmer guidance. This paper gives an insight of the innovative technologies in agriculture like culturing of specialized bacteria, alternative fertilizer technologies, inducement of information technology, hopefully it will provide a better projection for sustainable food and agriculture